Hubungan Sosial Ekonomi dan Pola Makan Dengan Kejadian Stunting Pada Balita di Desa Pringga Jurang Wilayah Kerja Puskesmas Montong Betok (Wellness And Healthy Magazine, 2021)
Background: Stunting according to WHO Child Growth Standards at index (PB/U) or age (TB/U) with a limit (z-score) less than -2 SD. From the 2018 Nutrition Status monitoring data, West Nusa Tenggara Province (2019) currently it is still recorded at 33.5%. It's much better than the previous year. However, this figure is still above the national figure of 29.6%. Objective: To determine the relationship between socioeconomic status and diet with the incidence of stunting in children under five in Pringga Jurang Village, Montong Betok Health Center Working Area. Methods:  The research used in this study is a  descriptive analytic study with a  cross-sectional approach. The sample in this study amounted to 65 children under five who were obtained by the total sampling technique. This research was conducted in June 2021. Data was collected through measuring height and distributing questionnaires. Data analysis was performed by chi-square test. Results: The results of the Chi-quare statistical analysis of socioeconomic with stunting obtained p value = 0.595 more than 0.05 from these results there was no relationship between socioeconomic and stunting in toddlers and diet with stunting obtained p value = 0.005 less than 0, 05 of these results there is a significant relationship between diet and stunting in toddlers. Conclusion: Socio-economy does not guarantee consuming food with less nutrition so it does not affect stunting, Lack of knowledge of mothers about the quality of food ingredients that are processed properly and correctly during the cooking process which requires it to be given at the right time, Prevention of stunting in toddlers needs to be improved to prevent occurrence of stunting in toddlers. Abstrak: Latar Belakang : Stunting menurut WHO Child Growth Standart pada indeks (PB/U) atau umur (TB/U) dengan batas (z-score) kurang dari -2 SD. Dari data pemantauan Status Gizi 2018, Provinsi Nusa Tenggara Barat, (2019) saat ini masih tercatat 33,5%. Sudah jauh lebih baik jika dibandingkan tahun sebelumnya. Namun angka tersebut masih diatas angka nasional sebesar 29,6% Tujuan :  Untuk  mengetahui Hubungan Status sosial ekonomi  dan pola  makan dengan  kejadian stunting pada Balita Di Desa Pringga Jurang, Wilayah Kerja Puskesmas Montong Betok. Metode : Penelitian yang digunakan pada penelitian ini adalah penelitian deskriptif analitik dengan pendekatan Cross-sectional. Sampel pada penelitian ini berjumlah 65 balita yang didapat dengan teknik Total sampling. Penelitian ini dilakukan pada bulan Juni 2021. Pengumpulan data dilakukan melalui pengukuran tinggi badan dan pembagian kuesioner. Analisis data dilakukan dengan uji chi-square. Hasil : Hasil analisis uji statistik Chi-square sosial ekonomi dengan stunting di dapatkan nilai p=0,595 lebih dari 0,05 dari hasil tersebut  tidak terdapat hubungan antara sosial ekonomi dengan stunting pada balita Dan pola makan dengan stunting di dapatkan nilai p=0,005 kurang dari 0,05 dari hasil tersebut terdapat hubungan yang signifikan antara pola makan dengan stunting pada balita. Kesimpulan : Sosial ekonomi tidak menjamin mengkonsumsi makanan dengan gizi kurang sehingga tidak berpengaruh terhadap stunting, Kurangnya pengetahuan ibu tentang kualitas bahan makanan yang diolah secara baik dan benar pada saat proses pemasakan yang mengharuskan diberikan pada waktu yang tepat, Pencegahan stunting pada balita perlu ditingkatkan untuk mencegah terjadinya stunting pada balita.